Avaliação da ação bioinseticida de SBTI e vicilina de Erythrina velutina em enzimas digestivas e membrana peritrófica de larvas de Plodia interpunctella (Lepidoptera: Pyralidae) - Amorim, Ticiana Maria Lúcio de (2007)
Plodia interpunctella (Indian meal moth) is a cosmopolitan pest that attacks not only a wide range of stored grain as well other food products. Due to its economic importance several researches have focused in a method with ability to control this pest with few or no damage to the environment. The study of digestive enzymes inhibitors, lectins and chitin-binding proteins, has often been proposed as an alternative to reduce insect damage. In this study we report the major classes of digestive enzymes during larval growth in P. Interpunctella, being those proteinases actives at pH 9.5 and optimum temperature of 50 oC to both larvae of the 3rd instar and pre-pupal stage of development. In vitro and zymogram assays presented the effects of several inhibitors, such as SBTI, TLCK and PMSF to intestinal homogenate of 3rd instar larvae of 62%, 92% and 87% of inhibition and In pre-pupal stage of 87%, 62 % and 55% of inhibition, respectively. Zymograms showed inhibition of two low molecular masses protein bands by TLCK and that in presence of SBTI were retarded. These results are indicative of predominance of digestive serine proteinases in gut homogenate from Plodia interpunctella larvae. This serine proteinase was then used as a target to evaluate the effect of SBTI on larvae in in vivo assay. Effect of SBTI on mortality and larval mass was not observed at until 4% of concentration (w/w) in diets. Chitin, another target to insecticidal proteins, was observed by chemical method. Moreover, optic microscopy confirmed the presence of a peritrophic membrane. Established this target, in vivo effect of EvV, a chitin binding vicilin, evaluated during the larval development of P. interpunctella and was obtained a LD50 of 0,23% and WD50 of 0,27% to this protein. Mechanism of action was proposed through of the in vivo digestibility of EvV methodology. During the passage through the larval digestive tract was observed that EvV was susceptible to digestive enzymes and a reactive fragment, visualized by Western blotting, produced by digestion was recovered after dissociation of the peritrophic membrane. The bound of EvV to peritrophic membrane was confirmed by immunohystochemical assays that showed strong immunofluorescent signal of EvV-FITC binding and peritrophic membrane. These results are a indicative that vicilins could be utilized as potential insecticide to Plodia interpunctella and a control methods using EvV as bioinsecticide should be studied to reduce lost caused by storage insect pests